2007
DOI: 10.1111/j.1740-8261.2007.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Diagnosis—degenerative Intraspinal Cyst Associated With an Intervertebral Disc

Abstract: A 6-year-old neutered male Rottweiler had chronic episodic signs of thoracolumbar pain and inability to stand that did not improve after rest and nonsteroidal antiinflammatory medication. In magnetic resonance images, an extradural mass was identified between the spinal cord and the T13/L1 intervertebral disc; the mass was compressing the cord in a dorsoventral direction. The lesion had a low signal intensity rim that enhanced slightly after gadolinium administration, and contents with similar signal intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
(52 reference statements)
3
20
0
Order By: Relevance
“…As with meningeal cysts, histopathology should remain the gold standard in defining these lesions, and this classification provides a robust scheme to classify extramedullary spinal cysts in the clinic. We found complete reports on 60 such intraspinal cysts in 24 dogs …”
Section: Non‐meningeal Extradural Cystsmentioning
confidence: 91%
See 4 more Smart Citations
“…As with meningeal cysts, histopathology should remain the gold standard in defining these lesions, and this classification provides a robust scheme to classify extramedullary spinal cysts in the clinic. We found complete reports on 60 such intraspinal cysts in 24 dogs …”
Section: Non‐meningeal Extradural Cystsmentioning
confidence: 91%
“…Intraspinal cysts may arise from either the annulus fibrosus or dorsal longitudinal ligament, although they remain uncommon compared to intraspinal synovial cysts of the intervertebral joints Penning et al reported an intraspinal cyst arising from the annulus fibrosus in a dog with features similar to those reported in people. The pathophysiology is considered similar to that which results in intraspinal cyst formation of the vertebral joints .…”
Section: Non‐meningeal Extradural Cystsmentioning
confidence: 94%
See 3 more Smart Citations